Juridical Evaluation of Articles 112 and 127 of Law Number 35 of 2009 Concerning Narcotics - Daulay, Cinthya Audi; Siregar, Taufik; Isnaini, Isnaini (Borong Newinera Publisher, 2025)
This study aims to evaluate the application of Articles 112 and 127 in Law Number 35 of 2009 concerning Narcotics and analyze judges' considerations in the application of law and evidence in cases recorded in Decision Number: 154/Pid.Sus/2023/PN.Bnj and Decision Number: 294/Pid.Sus/2023/PN.Bnj. This research uses qualitative research methods with a normative juridical approach and case studies. The results of the study show that the application of Article 112 often does not distinguish between users and drug dealers, so that drug users are often sentenced to heavier penalties even if they are not involved in narcotics trafficking. Meanwhile, Article 127 which provides space for rehabilitation has not been consistently applied by judges in handling cases of narcotics users. Analysis of the two decisions shows that there are inconsistencies in the use of Articles 112 and 127, which have implications for justice for perpetrators of narcotics crimes. Therefore, it is recommended that judges consider the rehabilitation factor for drug users more and not only focus on prison sentences. This research is expected to contribute to the development of a fairer and more humane narcotics law policy in Indonesia.